Numerical simulation of the oscillating thin plate impact on nanofluids flow in channel - Jehhef Kadhum Audaa; Rasheed Musaab Kadem; Siba Mohamed Abed Al Abas (Chemical Industry and Chemical Engineering Quarterly, 2024)
The present numerical study aims to present the effect of a titled oscillating thin plate with different inclination angles on the Al2O3-water nanofluid flow and heat transfer performance. The subsequent work establishes methods for forming fluid-structure interactions by the impact of Al2O3-water nanofluid at 0.1-1.0 vol. % volume fraction upon the thin plate using COMSOL Multiphysics 5.4. The turbulent model is solved using the (k-ε) model, and the flow assembly around the thin plate obstacle has been confirmed at the Reynolds number of Re=4×104. It exemplifies how Nanofluid flow interaction can distort structures. The turbulent, two-dimensional, stationary, and incompressible flow around an oscillating thin plate with inclined angles with upstream and downstream mounted inside a horizontal channel was studied. The numerical study includes an investigation of the effect of five inclination angles of the thin plate (30, 60, 90, 120, and 150°) on the pressure, velocity, and temperature contours of the Al2O3-water nanofluid. Also, the study presented the drag profile and left a force on the thin plate caused by the fluid flow. The results showed that a titled oscillating thin plate inside the flow direction increases pressure drop, von Mises deformation stress, x-displacement and drag force fields, and the Nusselt number. Where the pressure increased from 2.61×103 to 6.21×103 pa, the von Mises stress increased from 4.43×106 to 1.78×107 N/m, and the X-displacement increased from 1.6 to 5.5 mm when increasing the plate angle from 30 to 90°.